PENGUNGKAPAN EMISI KARBON SEBAGAI MEKANISME PENINGKATAN KINERJA UNTUK MENCIPTAKAN NILAI PERUSAHAAN - Chen Kelvin; Fransiskus E. Daromes; Suwandi Ng (Faculty of Economic and Business Universitas STIKUBANK, 2017)
The purpose of this research was to investigate the effect of carbon emissions disclosure on financial performance, operational performance and cost of equity, the influence of financial performance, operational performance, and cost of equity on firm value, and to investigate the effect of carbon emissions disclosure on firm value mediated by financial performance, operational performance, and cost of equity. Population used is the whole company public listed in Indonesia Stock Exchange period 2013- 2015. Number of samples are 86 firms each year, was selected by purposive sampling method and using secondary data, i.e. the annual report. The analytical method used is path analysis and hypothesis mediation analysed by using Sobel test. The result of analysis show that carbon emissions disclosure have positive and significant effect on financial performance, operational performance and cost of equity. While financial performancebhave positive but not significant effect on firm value, operational performance have positive and significant effect onfirm value, and cost of equityhave negative and significant effect on firm value. This research also shows that the operational performance and cost of equity plays a role in mediating carbon emissions disclosure on firm value, while financial performance do not mediate the effect of carbon emissions disclosure on firm value. The implication is the firms should pay more attention to the company's relationship with the surrounding environment so that the company's image can be improved because the firm’s sustainability are not only determined by the level of profitability, but also they have to combine economic performance, the concentration of social justice, and responsibility towards environmental sustainability. Keywords: carbon emissions disclosure, financial performance, operational performance, cost of equity and firm value